Microwave-induced One-pot Synthesis of 2,4,5-trisubstituted Imidazoles Using Rochelle Salt as a Green Novel Catalyst - Balasaheb V. Shitole; Nana V. Shitole; Suraj B. Ade; Gopal K. Kakde (Orbital: The Electronic Journal of Chemistry, 2015)
Rochelle Salt is used as an efficient catalyst for the synthesis of 2,4,5-triaryl-1H-imidazoles via condensation of benzil, ammonium acetate, and aromatic aldehydes. The key advantages of this process are the usage of an inexpensive and readily available catalyst, simple procedure, shorter reaction time, and high yield of products.DOI: http://dx.doi.org/10.17807/orbital.v7i3.720